7 Rights of Individuation: The Need for Greater Protection of Individual Rights in Big Data - Sampson, Fraser (Proceedings of the 2014 IEEE/ACM 7th International Conference on Utility and Cloud Computing, 2014)
Big Data have created a number of challenges in relation to the management of their complexity and variability, mainly by their aggregation and synthesis. This paper focuses on the different aspects of individuality that are affected by the use of Big Data. Specifically, it proposes in detail specific individual rights of data subjects that might not be sufficiently protected in relation to the use of Big Data. A number of conclusions are drawn that show the necessity for the EU legal framework to adapt to the new challenges posed by the use of Big Data.